LEARNING TO LISTEN TO PRIMARY SCHOOL CHILDREN - Halimatussakdiah Halimatussakdiah (Universitas Negeri Medan, 2023)
Abstract: Listening Learning in Elementary Children in Siosar Relocation National. Strategic Research Objectives. This institution is to improve the learning outcomes of listening to children by applying learning media to the story calendar. The research method in this study is qualitative exploratory. Data sources are children of victims of the Sinabung disaster who were relocated at Siosar class II and III SD. Data writing techniques are in the form of tests and field notes. Research instruments are performance tests and observation sheets. Research contributions are: so that teachers can practice the ability to listen to children, teachers are motivated to make innovative learning media, for schools can provide input in efforts to improve the learning outcomes of Indonesian class II and III elementary school, and provide consideration in the procurement of learning media in school .Keywords: Listening Learning, Elementary School Children.Abstrak: Pembelajaran Menyimak pada Anak SD di Relokasi Siosar. Tujuan Penelitian Strategis Nasional. Lembaga ini bertujuan untuk meningkatkan hasil belajar menyimak anak dengan menerapkan media pembelajaran kalender cerita. Metode penelitian dalam penelitian ini adalah kualitatif eksploratif. Sumber data adalah anak-anak korban bencana Sinabung yang direlokasi di SD Siosar kelas II dan III. Teknik penulisan data berupa tes dan catatan lapangan. Instrumen penelitian berupa tes unjuk kerja dan lembar observasi. Kontribusi penelitiannya adalah: agar guru dapat melatih kemampuan mendengarkan anak, guru termotivasi untuk membuat media pembelajaran yang inovatif, agar sekolah dapat memberikan masukan dalam upaya meningkatkan hasil belajar bahasa Indonesia kelas II dan III SD, dan memberikan pertimbangan dalam pengadaan media pembelajaran di sekolah.Kata Kunci: Pembelajaran Mendengarkan, Anak Sekolah Dasa